Smoking and Breast Cancer Recurrence after Breast Conservation Therapy - Jennifer D. Bishop; Brigid K. Killelea; Anees B. Chagpar; Nina R. Horowitz; Donald R. Lannin (International Journal of Breast Cancer)
Background. Prior studies have shown earlier recurrence and decreased survival in patients with head and neck cancer who smoked while undergoing radiation therapy. The purpose of the current study was to determine whether smoking status at the time of partial mastectomy and radiation therapy for breast cancer affected recurrence or survival. Method. A single institution retrospective chart review was performed to correlate smoking status with patient demographics, tumor characteristics, and outcomes for patients undergoing partial mastectomy and radiation therapy. Results. There were 624 patients who underwent breast conservation surgery between 2002 and 2010 for whom smoking history and follow-up data were available. Smoking status was associated with race, patient age, and tumor stage, but not with grade, histology, or receptor status. African American women were more likely to be current smokers (22% versus 7%, P<0.001). With a mean follow-up of 45 months, recurrence was significantly higher in current smokers compared to former or never smokers (P=0.039). In a multivariate model adjusted for race and tumor stage, recurrence among current smokers was 6.7 times that of never smokers (CI 2.0–22.4). Conclusions. Although the numbers are small, this study suggests that smoking may negatively influence recurrence rates after partial mastectomy and radiation therapy. A larger study is needed to confirm these observations.